CpG-A induces liquid–liquid phase separation of HMGB1 to activate the RAGE-mediated inflammatory pathway - Kaihui Peng; Gaohong Fu; Long Chen; Jiazhi Xie; Kai Bao; Jin-Ping Li; Shi-Zhong Luo (Proceedings of the National Academy of Sciences, 2025)
High-mobility group box protein 1 (HMGB1) is a chromatin-associated nonhistone protein widely distributed in the nucleus of eukaryotic cells. It is transported extracellularly as a proinflammatory mediator or late warning protein to induce immune and inflammatory reactions upon stimuli such as microbial infection. Here, we have found that HMGB1 directly interacts with bacterial DNA analogue CpG-A in the extracellular environment to undergo liquid–liquid phase separation (LLPS) via its positively charged DNA-binding domain. We have demonstrated that the receptor for advanced glycosylation end products (RAGE) responds to stimulation of the extracellular HMGB1-CpG-A complex and triggers phase separation of the downstream adaptor protein, Src76kDa structural domain leukocyte protein (SLP76), which promotes activation of the MAPK pathway and release of inflammatory cytokines. These results not only designate that LLPS serves as a gain-of-function mechanism involved in the axis of DNA-HMGB1 stimulated RAGE-SLP76 signaling pathway but also provide evidence that the activity of HMGB1 is regulated by LLPS, highly relevant to immune responses of inflammatory cells toward microbial infection. Especially, the finding that the intracellular SLP76 forms condensates with the cytosol domain of RAGE may represent a general downstream phenomenon when an inflammatory cell membrane receptor is activated.